A Comparative Study of Memory, Attention, Cognition and Oestradiol in Pre and Postmenopausal Women in Bangladesh (Bangladesh Pharmaceutical Journal, 2021)
Memory, attention, and cognitive dysfunction are psychopathological conditions which most commonly occur after menopause. Different clinical studies revealed a shred of substantial evidence that oxidative stress and estrogen are interlinked in various cognitive dysfunction, including memory impairment, age-related dementia, and Alzheimer's disease. There is a higher chance of developing cardiovascular disease after menopause. Sharp declines in concentrations of circulating estradiol and estrone are associated with menopause. Estrogen replacement therapy (ERT) enhances the blood circulation to the hippocampus and cortex, providing the optimum environment for the growth and survival of cholinergic neurons. Hence, it improves hippocampal neuron density and ultimately contributes to synaptic plasticity in the hippocampus enhances short and long-term memory. In this study, we assessed memory, attention, and cognition function between pre- and post-menopausal groups. After preliminary screening and applying exclusion criteria, fifteen premenopausal women and fifteen postmenopausal women were finally selected. Different neuropsychological tests such as logical memory test, digit span test, letter cancellation test, trail making test and Stroop test were performed to evaluate the memory, attention, and cognition status. Blood estradiol level was also assessed by using commercial kits. Significant difference (p